A Perioperative Paradigm of Cranioplasty With Polyetheretherketone: Comprehensive Management for Preventing Postoperative Complications - He, Zhenghui; Ma, Yuxiao; Yang, Chun; Hui, Jiyuan; Mao, Qing; Gao, Guoyi; Jiang, Jiyao; Feng, Junfeng (Frontiers in Surgery, 2022)
Introduction: At present, lots of studies have discussed the effects and outcomes of cranioplasty using polyetheretherketone (PEEK). However, interventions or management for PEEK cranioplasty got less attention. This article presented a perioperative paradigm for preventing postoperative complications. Materials and Methods: Modified PEEK plates with certified safety were implanted in patients who received evolving perioperative paradigm. Serial perioperative managements were developed as a comprehensive paradigm to prevent correlated risk factors of postoperative complications, which mainly included managements of epidural collections and wound healing. The preparation of the surgical area and systemic state were essential before surgery. During the operation, the blood supply of the incision and the handling of dura and temporalis were highlighted in our paradigm. After cranioplasty, management of subcutaneous drainage and wound healing were stressed. Patients received conventional management from February 2017 to August 2018 in our center. After the evolving paradigm developed, patients received comprehensive perioperative management from September 2018 to August 2020. Results: A total of 104 patients who underwent PEEK cranioplasty were consecutively enrolled; 38 (36.5%) received conventional perioperative management, and 66 (63.5%) received evolving perioperative paradigm. The general information of the two groups was comparable. Notably, patients who received the evolving paradigm presented a significantly decreased incidence of postoperative complications from 47.4% to 18.2% (P < 0.01), among which the incidences of subcutaneous effusion, epidural hematoma, and subcutaneous infection decreased significantly. Conclusion: The evolving perioperative paradigm could effectively prevent risk factors and reduce related complications. It was valuable to promote these comprehensive managements and inspire more clinical practice on improving patients’ outcomes after PEEK cranioplasty.